A Malaysian expert consensus on the use of high-sensitivity cardiac troponin in the emergency department - Raja Shariff, Raja Ezman; Kasim, Sazzli; Thambiah, Subashini C; Osman, Adi; Said, Asri; Jamaluddin, Farhi Ain; Mohd Salleh, Farina; Abd Karim, Sarah (Radcliffe Medical Media, 2022)
Recent guidelines have recommended using high sensitivity cardiac troponin (hs-cTn) assays to triage patients with suspected acute coronary syndrome. Despite this, less sensitive point-of-care testing is often the preferred choice in majority of hospitals. The aim of this evidence-based, expert consensus is to provide guidance for healthcare professionals in understanding the role of hs-cTn, specifically its level of sensitivity and specificity as well as its practical application in the emergency department setting, particularly in resource-limited centres in Malaysia. An expert panel with clinical and research expertise in the diagnosis and treatment of acute coronary syndrome was convened. Recommendations were based on a comprehensive review of the existing literature using MEDLINE and Embase databases, alongside individual clinical experience within the regional and international context. This expert consensus provides a structured approach to using hs-cTn in the emergency department and remains the only one to date produced by a group of Malaysian experts to help guide Malaysian clinicians dealing with acute chest pain on a daily basis.